Factors Associated with Streptococcus pneumoniae Nasopharyngeal Carriage and Antimicrobial Susceptibility among Children Under the Age of 5 Years in the Southwestern Colombia - Gámez, Gustavo; Rojas, Juan Pablo; Cardona, Santiago; Castillo Noreña, Juan David; Palacio, María Alejandra; Mejía, Luis Fernando; Torres, José Luis; Contreras, Jaime; Muñoz, Laura Mery; Criales, Javier; Vélez, Luis Felipe; Forero, Angélica María; Zúñiga, Yulieth Alexandra; Cuastumal, María Eugenia; Acevedo, Leidy Johanna; Molina, Álvaro de Jesús; Bolivar, Johan Alexis; Gómez-Mejia, Alejandro; Morales, Jessica Lorena; Hammerschmidt, Sven (Journal of Pediatric Infectious Diseases, 2021)
Objective This work aimed to evaluate the factors associated with Streptococcus pneumoniae nasopharyngeal colonization and antimicrobial susceptibility among pediatric outpatients in southwestern Colombia, 2019.Methods A cross-sectional study was performed using survey-based interviews and the collection of nasopharyngeal-swab specimens for microbiological characterization and antimicrobial susceptibility testing. Logistic regression analyses were performed for factors associated with nasopharyngeal carriage.Results A total of 452 children under the age of 5 years were examined in which 41.8% carried S. pneumoniae. Higher pneumococcal carriage frequencies were observed among participants aged <2 years and in individuals belonging to indigenous communities, which were lacking established pneumococcal-conjugated vaccine-10 immunization schemes. Additionally, children attending childcare institutions were also highly colonized by pneumococci. S. pneumoniae showed 57.7% nonsusceptibility to benzyl-penicillin (meningitis-cut); 45.5% intermediate-sensitivity to benzyl-penicillin (oral-cut) and 21.7% to cefotaxime; and resistance to erythromycin (40.7%), tetracycline (36.0%), trimethoprim/sulfamethoxazole (24.9%), clindamycin (24.3%), and ceftriaxone (27.0%).Conclusion The 41.8% of participants carrying S. pneumoniae show a scenario with the presence of multidrug and extensively drug-resistant strains, which constitutes important reservoirs of bacterial transmission by children aged <5 years in Colombia, leading to an onset of pneumococcal diseases. Hence, there is an urgent need to expand conjugate pneumococcal immunization in the community and ensure compliance with established immunization schedules.
Keywords: Streptococcus pneumoniae; pneumococcal children colonization; nasopharyngeal carriage; Colombia